2008
DOI: 10.1097/01.ncq.0000314728.65721.7c
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-Friendly Hospital Project

Abstract: The present shortage of nurses in the United States is expected to continue. Nurse shortage, the nature of the work environment, and employers' expectations and attitudes, among other factors, influence both nurse retention and quality of patient care. The Nurse-Friendly Hospital Project was designed to improve nurses' work environment in rural and small hospitals in Texas. Findings demonstrate improvements in nurse retention, nurse staffing, and quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The nurse-friendly hospital criteria index, which is known as the Adapted Nursing Work Index-Revised (Adapted NWI-R), was prepared in 2008 by Meraviglia et al. [21] by reviewing the items of the Nursing Work Index–Revised (NWI-R) and the Practice Environment Scale and by matching the appropriate items for each nurse-friendly hospital criterion with the help of specialists. Adapted NWI-R consists of 30 items and 12 sub-criteria [21].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nurse-friendly hospital criteria index, which is known as the Adapted Nursing Work Index-Revised (Adapted NWI-R), was prepared in 2008 by Meraviglia et al. [21] by reviewing the items of the Nursing Work Index–Revised (NWI-R) and the Practice Environment Scale and by matching the appropriate items for each nurse-friendly hospital criterion with the help of specialists. Adapted NWI-R consists of 30 items and 12 sub-criteria [21].…”
Section: Methodsmentioning
confidence: 99%
“…The Texas Nurses Association defined nurse-friendly hospital criteria as tools for creating a supportive healthy/positive work environment for hospitals that do not meet the magnet hospital criteria. The nurse-friendly hospital criteria consist of twelve main items, namely, control over nursing practice, safety of work environment, presence of systems dealing with patient care, nurse orientation, qualification of head nurses, professional development, competitive wages, nurse respect/recognition, balanced lifestyle, zero tolerance to nurse abuse policy, middle management responsibility and quality initiatives [15,21]. Several of the Nursing Sensitive Criteria for the Selection of European Centres of Excellence of the European Federation of Nurses Associations refer to nurse-friendly hospital criteria [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 A study in rural/small hospitals which implemented 12 nurse-friendly criteria to create a positive work environment observed positive changes in nurses’ perception of their work environment and improvements in quality of care in participating hospitals postintervention. 86 A hospital-based intervention study to change organisational culture on frequency of staff handwashing did not improve rates of methicillin-resistant Staphylococcus aureus in two hospitals, but rates of vancomycin-resistant enterococci were significantly reduced in the intervention hospital during implementation. 90 A prominent interventional study, the UK Safer Patients Initiative, indicated that while there was a small improvement in staff attitudes to organisational climate in intervention hospitals, the intervention had no significant effect on patient safety outcomes, measured by the proportion of prescription errors, rates of adverse events and mortality rates.…”
Section: Resultsmentioning
confidence: 93%
“…Another review also described two studies demonstrating a positive impact of one year team oriented interventions (one of team discussion groups, the other undefined) on turnover [ 33 ]. Nursing practice models, for example nurse-managed units and unit-level self-management widely used by hospitals with Magnet accreditation in North America [ 43 - 45 ] were reported to have mixed evidence of effect [ 33 ].…”
Section: Findings On Interventions To Reduce Turnover In Adult Nursinmentioning
confidence: 99%